Elevated Water Tank Design Comparison in Different Seismic Zones (International Journal of Innovative Research in Computer Science & Technology, 2022)
Water is maintained in tall tanks as part of  the public water system. Because of a shortage of water or  difficulties putting out a fire after an earthquake, the collapse  of these water tanks could pose major risks to people.  According to draught code Part II of IS 1893:2002, twelve  raised circular and H-intake storage tanks with a combined  capacity of two lakh litres each would be studied in this  study. STAAD Pro V8i is used to conduct a response  spectrum analysis of elevated circular and H-shaped water  intake tanks in seismic zones II and V. A comparison was  made between each collected value for the base shear axial  force and lateral displacements. There is a divergence in the  H-tank and a negligible variance, according to analysis of a  comparison of two water tanks.
Keywords: Elevated Circular Water Tank; Elevated H Intake Water Tank; Response Spectrum Analysis